IMPLEMENTASI PROGRAM BUSINESS CENTER (BC) SEBAGAI UPAYA PENINGKATAN MUTU PENDIDIKAN SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI I KEBUMEN (JURNAL ILMIAH TUT WURI HANDAYANI, 2013)
The learning based on the social interaction is very important to solve any problems in the school or people. People always do hope that one of place giving the student creating character is school so it can produce the good alumni having a good character. The entrepreneurship is a knowledge that can read the environment and can create the ready entrepreneur everywhere. Based on the fact above, Business Center (BC) is a place for entrepreneurship learning in the social interaction or the economic production so it can answer the education problems.